Mr. Selfridge. Season 2 [videorecording (DVD)] - Davies, Andrew, 1936- (2014)
Much has changed since Selfridges first opened its doors. Five years later, Europe is on the brink of war and London is enjoying one last defiant period of decadence. Mr. Selfridge now has his sights set on joining the establishment and rebuilding his family life. Tensions are also running high on the shop floor as Agnes is back from Paris, chic and successful. Not everyone is thrilled by her newfound confidence and by the reappearance of her old ally Henri Leclair, returned from America.